Faecal transplantation and Clostridioides difficile infection - Knežević Darija A. (Medical Society of the Republic of Srpska, Banja Luka, University of Banja Luka. Faculty of Medicine, 2021)
Faecal microbiota transplantation (FMT), known equally well as faecal transplantation or faecal bacteriotherapy, is the process of implanting the faecal suspension containing balanced microbiota from a healthy donor to the colon of a recipient patient. Excessive growth of Clostridioides difficile (C difficile) in the intestinal microbiota resulting from antibiotic consumption is currently a rising threat to public health. FMT is one of the most important, newer approaches to treating C difficile infections. Since C difficile is regarded as an opportunistic bacterium triggering disease in conditions of disturbed homeostasis of the intestinal microbiota, restoration of healthy intestinal microflora facilitates suppression of toxic strain of C difficile by anaerobic bacteria of normal intestinal microflora with concomitant cure. Nurses have important role in caring for patients after faecal transplantation.